PELATIHAN MEMBANGUN JEJARING PEMASARAN PADA MASA PANDEMI UMKM KAB. BATANG - Danang Satrio; Choliq Sabana (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Covid 19 has a considerable impact in various sectors in Indonesia, especially in the field of MSMEs. UMKM in Batang Regency in their work facing both internal and external problems so that MSMEs have not been able to provide optimal contributions like other economic institutions. One of the problems is the limitation of MSMEs in accessing information and market coverage, labor networks, and access to strategic locations for businesses during the Covid 19 Pandemic. The goal to be achieved is to improve the performance of MSMEs in Batang Regency with the presence of entrepreneurial networks. The specific goal to be achieved is to improve the performance of MSMEs throughout Batang Regency with the application of entrepreneurial networks. The importance of this service is expected to increase the performance of MSMEs through exploratory learning of human resources, encourage efficient use of resources, increase planning and implementation capacity to solve problems, improve network cooperation (networking) in collaboration with business partners and increase competitiveness, providing better service to clients and customers.Keywords: Marketing Network, Covid 19, MSMEs